Workplace bullying in the UK NHS: a questionnaire and interview study on prevalence, impact and barriers to reporting. Issue 6 (1st July 2013) - Carter, Madeline; Thompson, Neill; Crampton, Paul; Morrow, Gill; Burford, Bryan; Gray, Christopher; Illing, Jan
Abstract : Objectives: To examine the prevalence and impact of bullying behaviours between staff in the National Health Service (NHS) workplace, and to explore the barriers to reporting bullying. Design: Cross-sectional questionnaire and semi-structured interview. Setting: 7 NHS trusts in the North East of England. Participants: 2950 NHS staff, of whom 43 took part in a telephone interview. Main outcome measures: Prevalence of bullying was measured by the revised Negative Acts Questionnaire (NAQ-R) and the impact of bullying was measured using indicators of psychological distress (General Health Questionnaire, GHQ-12), intentions to leave work, job satisfaction and self-reported sickness absence. Barriers to reporting bullying and sources of bullying were also examined. Results: Overall, 20% of staff reported having been bullied by other staff to some degree and 43% reported having witnessed bullying in the last 6 months. Male staff and staff with disabilities reported higher levels of bullying. There were no overall differences due to ethnicity, but some differences were detected on several negative behaviours. Bullying and witnessing bullying were associated with lower levels of psychological health and job satisfaction, and higher levels of intention to leave work. Managers were the most common source of bullying. Main barriers to reporting bullying were the perception that nothing would change, not wanting to be seen as a trouble-maker, the seniority of the bully and uncertainty over how policies would be implemented and bullying cases managed. Data from qualitative interviews supported these findings and identified workload pressures and organisational culture as factors contributing to workplace bullying. Conclusions: Bullying is a persistent problem in healthcare organisations which has significant negative outcomes for individuals and organisations.